Patterns of specialization and escalation in the criminal careers of gang and non-gang homicide offenders - Adams, Jennifer J. (Criminal justice and behavior, 2014)
Although studies have established that homicide offenders are clearly well versed in the criminal world, there is limited knowledge of the specific types of offenses they engage in leading up to the homicide, and if patterns of specialization or escalation exist. In addition, no study on homicide offenders has differentiated between gang and non-gang members. This study examines the arrest histories of homicide gang and non-gang offenders to assess whether patterns of offense specialization, escalation, or de-escalation exist. The findings suggest that homicide offenders were heavily involved in violent and drug crimes prior to the homicide. Gang members committed and specialized in drug crimes, while non-gang members committed more violent crimes and had the highest probability of specializing in drug crimes. Theoretical and practical implications are discussed in light of these findings.